Rancang Bangun Pengendali Pintu, Kipas, Dan Lampu Pada Smarthome Menggunakan Fuzzy Logic dan Data Dashboard - Pierl Kritzenger Sinaga; Wijaya Kurniawan; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
House is an inseparable part of human life, the existence of a house to be a means of human activity. Human needs to get easy access to the device on Smarthome using smartphones and light control in order to improve the effectiveness and comfort of activities in the house. From these problems, in this study, house modeling and application of access to devices at home is required. The light adjustment made in the light feature is based on the intensity value using the Light Dependent Resistor and feature control via the NI Data Dashboard application on the smartphone, as well as using the DC motor as a fan and servo to move the door. As the main controller used NI MyRIO. This research uses Fuzzy logic method to determine the value of light to determine the value of light intensity issued by the lamp. Testing done with several different scenarios, system calculations compared with manual calculations, overall Fuzzy logic calculations on the lamp error percentage of 0% and 4 times sensor readout failure. While communication between systems with dashboard data has an average delay of 0.96 seconds, as well as interface display on dashboard data with a good 71% predicate.